2007
DOI: 10.2353/ajpath.2007.060835
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Vascular Endothelial Growth Factor-D in Lymphangiogenesis and Metastasis

Abstract: In many human carcinomas, expression of the lymphangiogenic factor vascular endothelial growth factor-D (VEGF-D) correlates with up-regulated lymphangiogenesis and regional lymph node metastasis. Here, we have used the Rip1Tag2 transgenic mouse model of pancreatic beta-cell carcinogenesis to investigate the functional role of VEGF-D in the induction of lymphangiogenesis and tumor progression. Expression of VEGF-D in beta cells of single-transgenic Rip1VEGF-D mice resulted in the formation of peri-insular lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 35 publications
4
76
0
1
Order By: Relevance
“…Angiogenesis and lymphangiogenesis are also crucial for tumor progression and nodal metastasis in OSCC [10]. Some of the main angiogenic and lymphangiogenic factors have been identified as vascular endothelial growth factor (VEGF)-A and VEGF receptor(VEGFR) 2, as well as the VEGF-C/-D and VFGFR3 systems, respectively [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis and lymphangiogenesis are also crucial for tumor progression and nodal metastasis in OSCC [10]. Some of the main angiogenic and lymphangiogenic factors have been identified as vascular endothelial growth factor (VEGF)-A and VEGF receptor(VEGFR) 2, as well as the VEGF-C/-D and VFGFR3 systems, respectively [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Expression levels of VEGF-D and VEGF-C correlate with lymph node metastasis in several human cancers [15,16], and addition or overexpression of exogenous VEGF-C or VEGF-D induces lymphatic growth and tumor metastasis in preclinical cancer models [17][18][19][20][21][22][23][24][25]. Addition of exogenous VEGF-D or VEGF-C also induces the formation of functional, mature collecting lymphatic collecting lymphatic vessels in mice [6].…”
Section: Introductionmentioning
confidence: 99%
“…Stacker et al [13] subsequently demonstrated in a mouse model that lymphatic spread was also associated with the expression of (VEGF-D) by the tumor. Kopfstein et al [14] further showed in a transgenic mouse model that VEGF-D, as it was expressed by the tumor cells, induced tumor lymphangiogenesis, lymph node metastasis and promoted metastasis to the lungs. Moreover, in a variety of human cancers, including gastric, pancreatic, lung, colorectal, breast and ovary, elevated tumoral VEGF-C and VEGF-D expression correlates with an increased incidence of regional lymph node metastasis and poor prognosis [15][16][17][18][19][20].…”
mentioning
confidence: 99%